ANALISIS KETERAMPILAN DASAR MENJELASKAN OLEH GURU DALAM MENGAJARKAN MEMBACA PERMULAAN SISWA TUNAGRAHITA DI SDLB KASIH IBU PEKANBARU - Dewi, Yunita Eka; Kurniaman, Otang (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The role of a teacher is so important in the learning process especially learning to read the beginning. Therefore, the role of a teacher greatly determines the success of students in learning to read the beginning, it is important for a teacher to have good teaching skills. One of these skills is explaining skills because in the learning process many demands the teacher can explain. The purpose of this study was to describe the teacher's explaining skills in teaching reading the beginnings of mentally retarded students at SDLB Kasih Ibu Pekanbaru. The research method used is qualitative research, this study tells of a symptom, event, or event that occurred now. Data obtained after the study can be seen that the teacher in applying explaining skills in teaching the beginning reading of mentally retarded students at SDLB Kasih Ibu Pekanbaru has been implemented quite well because the teacher has been able to carry out the components in explaining skills to achieve optimal learning.